Internationale Wissenschaftskommunikation und Nationalsozialismus Akademischer Austausch, Konferenzen und Reisen in Geistes- und Kulturwissenschaften 1933 bis 1945 - Albrecht, Andrea; Danneberg, Lutz; Klausnitzer, Ralf; Mateescu, Kristina (De Gruyter, 2022)
Taking a critical stance toward "internationality" was one of the central aspects of the notion of scholarship propagated in National Socialist Germany between 1933 and 1945. However, during this time, German scholars had surprisingly extensive contact with their international peers. This volume examines international academic relations by looking at research trips, world congresses, and bilateral conferences.